Faktor Risiko Riwayat Hipertensi dan Diabetes Mellitus Pada Ibu Hamil Terhadap Kejadian Preeklampsia di RSKD Ibu Anak Siti Fatimah 2021: Risk Factors for History of Hypertension and Diabetes Mellitus in Pregnant Women on Preeclampsia in Siti Fatimah Mother and Child Hospital 2021 - Fachrul, Moch. Afif; Andi Irhamnia Sakina; Nadyah Haruna (Jurnal Midwifery, 2024)
Introduction Preeclampsia is a condition where a pregnant woman having hypertension that occurs after 20 weeks of gestation accompanied with impaired organ function which can be marked by proteinuria. To this day, preeclampsia pose a very dangerous threat to pregnancy and has become the leading cause of death on pregnant women. The purpose of this study was to determine the relationship between risk factor of history of hypertension and diabetes mellitus of pregnant woman with the incidence of preeclampsia at Siti Fatimah Makassar Woman and Children Regional Special Hospital in 2021. Method This study was an analytic observational study with a case control approach. The sampling method was the total sampling technique and 182 samples which 91 case and 91 control were obtained through medical records. Result The result showed that of the 182 sample, there were 73 pregnant women (80,2%) with history of hypertension who had preeclampsia, 9 pregnant woman (4,9%) with diabetes mellitus who had preeclampsia. Conclusion History of hypertension is a risk factor for the incidence of preeclampsia and diabetes mellitus is not the risk factor for the incidence of preeclampsia.